Differential Effect of Nobiletin and Tangeretin on the Antioxidant Activity and Levels of α-Tocopherol and Retinol in Rats - Rodrigues, Marilia; Gonçalves, Danielle; Baeta, Danielli; Manthey, John; Cesar, Thais (Food Science and Engineering, 2021)
Polymethoxylated flavones (PMFs) have been associated with increased antioxidant activity in animal models. The effects of tangeretin (TAN) and nobiletin (NOB) on antioxidant activity in the blood and liver of rats were evaluated. Groups of rats were treated with 200 mg/kg bw/day of TAN or NOB, or placebo, for 15 days. Parental compounds and their metabolites were assessed in the liver by chromatographic analysis, in addition to α-tocopherol and retinol in the blood serum. Both TAN and NOB supplements were able to reduce malonaldehyde (MDA) in the rat’s blood by 22% and 18%, respectively, but only NOB increased redox reaction by 3%. Blood levels of retinol and α-tocopherol increased under TAN by 59% and 20%, respectively, but were not affected by NOB. Eight NOB metabolites were detected in the liver, but only two TAN metabolites were identified in low concentration. In conclusion, NOB improved antioxidant capacity and reduced lipid peroxidation, while increased levels of retinol and α-tocopherol after TAN supplement may have contributed to decreased blood lipid peroxidation.